Computer simulation of the enantioselective separation of weak bases in an online capillary electrophoresis based microanalysis configuration comprising sulfated cyclodextrin as selector. Issue 12 (4th May 2018) - Mikkonen, Saara; Thormann, Wolfgang
Abstract: Computer simulation was utilized to characterize the electrophoretic processes occurring after reactant mixing in an online assay format used for monitoring the enantioselective N ‐demethylation of ketamine to norketamine in the presence of highly sulfated γ‐cyclodextrin (HS‐γ‐CD). The incubated reaction mixture (at pH 7.4 and without chiral selector) is bracketed by a low pH BGE containing 2% HS‐γ‐CD as chiral selector, thereby forming a discontinuous buffer system. Upon power application, simulation provides insight into the formation of moving boundaries and new zones together with the prediction of the behavior of ketamine and norketamine enantiomers. The analytes first migrate cationically in a zone electrophoretic manner until they come in contact with HS‐γ‐CD upon which enantioseparation is initiated. Complexation has a focusing effect and the electrophoretic transport becomes reversed, that is, toward the anode. Simulation revealed that the initial conditions for the chiral separation, including buffer components concentrations, pH, and ionic strength, are different than those in the BGE. As a consequence thereof, the experimentally determined complexation parameters for the BGE were unable to correctly describe the migration behavior of the analytes in this column section. An increase in the input binding constants by a factor of two to four, as a result of the decreased ionic strength, resulted in simulation data that agreed with experimental findings.